Clinical trial for uniform multidrug therapy for leprosy patients in Brazil (U-MDT/CT-BR): adverse effects approach - Rossilene Conceição da Silva Cruz; Samira Bührer-Sékula; Gerson Oliveira Penna; Maria Elisabete Amaral de Moraes; Heitor de Sá Gonçalves; Mariane Martins de Araújo Stefani; Maria Lúcia Fernandes Penna; Maria Araci de Andrade Pontes; Sinésio Talhari (Sociedade Brasileira de Dermatologia, 2018)
Abstract: BACKGROUND: The Clinical Trial for Uniform Multidrug Therapy for Leprosy Patients in Brazil (U-MDT/CT-BR), designed to evaluate the effectiveness of a six-months regimen, assessed the adverse effects caused by the drugs. OBJECTIVE: Describe adverse effects due to MDT in U-MDT/CT-BR, comparing the uniform regimen (U-MDT) to the current WHO regimen (R-MDT). Patients and methods: After operational classification, patients were randomly allocated to the study groups. U-MDT PB and U-MDT MB groups, received the U-MDT regimen, six doses of MB-MDT (rifampicin, dapsone and clofazimine). R-MDT PB and R-MDT MB groups, received the WHO regimens: six doses (rifampicin and dapsone) for PB and 12 doses (rifampicin, dapsone and clofazimine) for MB. During treatment, patients returned monthly for clinical and laboratorial evaluation. Patients with single lesion were not included in this trial. RESULTS: Skin pigmentation (21.7%) and xerosis (16.9%) were the most frequent complaints among 753 patients. Laboratory exams showed hemoglobin concentration lower than 10g/dL in 23.3% of the patients, glutamic oxaloacetic transaminase (GOT) above 40U/L in 29.5% and glutamic pyruvic transaminase (GPT) above 40U/L in 28.5%. Twenty-four patients (3.2%) stopped dapsone intake due to adverse effects, of whom 16.6% due to severe anemia. One case of sulfone syndrome was reported. STUDY LIMITATIONS: Loss of some monthly laboratory sample collection. CONCLUSIONS: There was no statistical difference regarding adverse effects in the R-MDT and U-MDT groups but anemia was greater in patients from R-MDT/MB group, therefore adverse effects do not represent a constraint to recommend the six-month uniform regimen of treatment for all leprosy patients.